Analisis Kadar Air dan Laju Pengeringan Bahan Baku Pembuatan Bubur Pedas Instan - Suhendra, Suhendra; Nopriandy, Feby; Perdana, Daud; Maryam, Andi (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
Bubur pedas is a traditional food from Sambas Regency which is very popular in West Kalimantan. The development of bubur pedas was carried out by making instant bubur pedas so that this food can be enjoyed anytime and anywhere. The main problem found in the production process is in the drying process of raw materials. Based on these problems, it is necessary to develop a drying system to help the instant bubur pedas production process. Through this research, a performance test of a rotary drum type dryer was carried out to analyze the water content and drying rate of instant bubur pedas raw materials. The raw materials for dried instant bubur pedas are katuk leaves, singkil leaves and fern leaves. The rotary drum type dryer is operated at a rotational speed of 14.5 rpm. The drying process takes 2 hours with data collection every 20 minutes. Based on the measurement results, the initial water content of katuk leaves was 76.66%, singkil leaves were 72.72% and fern leaves were 88.06%. After drying for 2 hours, the water content of katuk leaves dropped to 38.40%, singkil leaves 43.91%, and fern leaves 64.64%. The material that experienced the highest decrease in water content was katuk leaves at 38.26%, followed by singkil leaves at 28.81% and fern leaves at 23.42%. The average drying rate for instant bubur pedas raw materials was fern leaves 0.1213 grams/second, katuk leaves 0.0613 grams/second and singkil leaves 0.0314 grams/second.